Safety and immunogenicity of Nanocovax, a SARS-CoV-2 recombinant spike protein vaccine: Interim results of a double-blind, randomised controlled phase 1 and 2 trial - Thuy P. Nguyen; Quyet Do; Lan T. Phan; Duc V. Dinh; Hiep Khong; Luong V. Hoang; Thuong V. Nguyen; Hung N. Pham; Men V. Chu; Toan T. Nguyen; Quang D. Pham; Tri M. Le; et al. (Elsevier, 2022)
Summary: Background: Nanocovax is a recombinant severe acute respiratory syndrome coronavirus 2 subunit vaccine composed of full-length prefusion stabilized recombinant SARS-CoV-2 spike glycoproteins (S-2P) and aluminium hydroxide adjuvant. Methods: We conducted a dose-escalation, open label trial (phase 1) and a randomized, double-blind, placebo-controlled trial (phase 2) to evaluate the safety and immunogenicity of the Nanocovax vaccine (in 25 mcg, 50 mcg, and 75 mcg doses, aluminium hydroxide adjuvanted (0·5 mg/dose) in 2-dose regime, 28 days apart (ClinicalTrials.gov number, NCT04683484). In phase 1, 60 participants received two intramuscular injection of the vaccine following dose-escalation procedure. The primary outcomes were reactogenicity and laboratory tests to evaluate the vaccine safety. In phase 2, 560 healthy adults received either vaccine doses similar in phase 1 (25 or 50 or 75 mcg S antigen in 0·5 mg aluminium per dose) or adjuvant (0·5 mg aluminium) in a ratio of 2:2:2:1. One primary outcome was the vaccine safety, including solicited adverse events for 7 day and unsolicited adverse events for 28 days after each injection as well as serious adverse event or adverse events of special interest throughout the study period. Another primary outcome was anti-S IgG antibody response (Index unit/ml). Secondary outcomes were surrogate virus neutralisation (inhibition percentage), wild-type SARS-CoV-2 neutralisation (dilution fold), and T-cell responses by intracellular staining for interferon gamma (IFNg). Anti-S IgG and neutralising antibody levels were compared with convalescent serum samples from symptomatic Covid-19 patients. Findings: For phase 1 study, no serious adverse events were observed for all 60 participants. Most adverse events were grade 1 and disappeared shortly after injection. For phase 2 study, after randomisation, 480 participants were assigned to receive the vaccine with adjuvant, and 80 participants were assigned to receive the placebo (adjuvant only). Reactogenicity was absent or mild in the majority of participants and of short duration (mean ≤3 days). Unsolicited adverse events were mild in most participants. There were no serious adverse events related to Nanocovax. Regarding the immunogenicity, Nanocovax induced robust anti-S antibody responses. In general, there humoral responses were similar among vaccine groups which reached their peaks at day 42 and declined afterward. At day 42, IgG levels of vaccine groups were 60·48 [CI95%: 51·12-71·55], 49·11 [41·26-58·46], 57·18 [48·4-67·5] compared to 7·10 [6·32-13·92] of convalescent samples. IgG levels reported here can be converted to WHO international standard binding antibody unit (BAU/ml) by multiplying them to a conversion factor of 21·8. Neutralising antibody titre of vaccine groups at day 42 were 89·2 [52·2-152·3], 80·0 [50·8-125.9] and 95·1 [63·1-143·6], compared to 55·1 [33·4-91·0] of the convalescent group. Interpretation: Up to day 90, Nanocovax was found to be safe, well tolerated, and induced robust immune responses. Funding: This work was funded by the Coalition for Epidemic Preparedness Innovations (CEPI), the Ministry of Science and Technology of Vietnam, and Nanogen Pharmaceutical Biotechnology JSC.